Global and Widespread Local White Matter Abnormalities in Juvenile Neuronal Ceroid Lipofuscinosis - Roine, U.; Roine, T.J.; Hakkarainen, A.; Tokola, A.; Balk, M.H.; Mannerkoski, M.; Åberg, L.E.; Lönnqvist, T.; Autti, T. (American journal of neuroradiology : AJNR, 2018)
Juvenile neuronal ceroid lipofuscinosis is a progressive neurodegenerative lysosomal storage disease of childhood. It manifests with loss of vision, seizures, and loss of cognitive and motor functions leading to premature death. Previous MR imaging studies have reported cerebral and cerebellar atrophy, progressive hippocampal atrophy, thalamic signal intensity alterations, and decreased white matter volume in the corona radiata. However, conventional MR imaging findings are usually normal at younger than 10 years of age. The purpose of our study was to investigate whether diffusion MR imaging could reveal changes in white matter microstructure already present at a younger age. We investigated global and local white matter abnormalities in 14 children with juvenile neuronal ceroid lipofuscinosis (mean age, 9.6 ± 3.4 years; 10 boys) and 14 control subjects (mean age, 11.2 ± 2.3 years; 7 boys). Twelve patients underwent follow-up MR imaging after 2 years (mean age, 11.4 ± 3.2 years; 8 boys). We performed a global analysis using 2 approaches: white matter tract skeleton and constrained spherical deconvolution-based whole-brain tractography. Then, we investigated local microstructural abnormalities using Tract-Based Spatial Statistics. We found globally decreased anisotropy ( = .000001) and increased diffusivity ( = .001) in patients with juvenile neuronal ceroid lipofuscinosis. In addition, we found widespread increased diffusivity and decreased anisotropy in, for example, the corona radiata ( < .001) and posterior thalamic radiation ( < .001). However, we found no differences between the first and second acquisitions. The patients with juvenile neuronal ceroid lipofuscinosis exhibited global and local abnormalities in white matter microstructure. Future studies could apply more specific microstructural models and study whether these abnormalities are already present at a younger age.